The Correlation Between Learning Environment in the Nursing Laboratory and Student Learning Satisfaction with the GPA of Third Semester Nursing Students - Dewi Ayu Lutfiah; Devita Elsanti; Ragil Setiyabudi (UM Purwokerto Press, 2024)
Background: In the learning process, its environment can affect students' concentration and information absorption, as well as their achievement of competencies. Student satisfaction with learning enhances their motivation to explore the material, thus improving their learning outcomes in terms of GPA.The purpose of this study is to determine the relationship between the learning environment in the nursing laboratory, student learning satisfaction, and the GPA of third-semester nursing students at the university. Method: This research is quantitative with an analytic correlation design and uses a cross-sectional approach. The sample was selected using purposive sampling with a total of 144 respondents. Univariate analysis is presented in frequency and percentage tables. Bivariate analysis employs the Pearson Product Moment test. Results: The results of the research using the Pearson Product Moment analysis show that the correlation coefficient (r) of 0.682 indicates a significant relationship between the learning environment in the laboratory and student satisfaction with learning in nursing. The correlation between the learning environment in the laboratory and students' GPA is 0.635, while the correlation between learning satisfaction and students' GPA is 0.434, indicating a fairly strong correlation between these two variables. Conclusion: The significant correlation (p) of 0.0001 indicates a strong positive correlation between the learning environment in the laboratory and learning satisfaction. The correlation between learning environment and students' GPA is strong, indicating that a better learning environment leads to higher GPAs. Additionally, the correlation between learning satisfaction and students' GPA is moderately strong.